Eosinophilic sialodochitis: An emerging atopic condition. (12th March 2021) - Carey, Barbara; O'Neill, Niall; Brown, Jackie; Escudier, Michael; Hullah, Esther; Beneng, Kiran; Odell, Edward; Thomas, Bethan; Haque, Rubaiyat
Abstract: Objective: To report the clinical characteristics of the largest single centre cohort of patients with eosinophilic sialodochitis. Methods: Analysis of data relating to 37 patients seen in a dedicated multidisciplinary clinic was performed. Demographic, clinical, haematological, cytological, histological and radiological features were collated. Response to trials of allergy treatment was assessed. Results: Thirty‐seven patients (30 female, seven male) were identified, 42% of whom were of Afro‐Caribbean origin, with a mean age of 50.4 years (range 28–80 years). Mean symptom duration at presentation was 10 years (range 2–33 years). Parotid and submandibular gland involvement was equally reported. The most commonly reported symptoms were swelling (97%), itching of the overlying skin (92%), salivary gland discomfort (84%) and "string‐like" mucus discharge from salivary duct orifices (76%). Twenty‐three patients (62%) demonstrated atopic disease and serum IgE level elevated in 57%. All 37 patients had eosinophils present in aspirated duct contents samples while raised peripheral eosinophil count was seen in 41%. Anecdotal symptom improvement was reported with antihistamine, antileukotriene or steroid treatment. Conclusion: Eosinophilic sialodochitis should be considered in any patient presenting with recurrent salivary gland swelling. Further studies are needed to evaluate treatments directed at a likely allergic pathogenesis.